Detection of sequence diversity in the CYP2C19 gene of Xhosa South African individuals : an analytical and comparative study including in silico and functional analysis of the 5’ flanking region - Drogemoller, Britt I. (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MSc (Genetics))--University of Stellenbosch, 2010.